Nicaragua Canal Construction Company records - Nicaragua Canal Construction Company
Chiefly survey notebooks kept during expeditions in Nicaragua by hydrographic and topographic survey teams investigating the nature, depth, and suitability of the rivers and waterways of Nicaragua for purposes of a canal. Also includes issues, 1911-1913, of the Canal Record, a newspaper published by the American administration of the Panama Canal Zone.
Library of Congress Geography and Map Division.
A corporate enterprise formed in 1886 to build the first trans-Isthmian canal across Central America.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Canal Zone; Canal record; Canals -- Central America; Rivers -- Nicaragua; Waterways -- Nicaragua; Panama Canal (Panama) -- Periodicals; Nicaragua -- Surveys